Vermicompostos as substrates in the seedlings performance of lettuce and arugula - Lima, Marcus Vinícius Gonçalves (2019)
Success in vegetables production is closely linked to the quality of seedlings, using substrates in placeof the soil in the formation of seedlings. The objective of this study was to evaluate the performance of lettuce and arugula seedlings using substrates produced with vermicompost along with sawdust and rice husks as conditioning agents. Two experiments were carried in Vilhena, Rondônia, using a completely randomized design, in a 3x2 factorial scheme with seven replicates, corresponding to three substrates and two cultivars, for both lettuce and arugula. The proportion of the material was 1: 3 of the total volume of soil, of poultry manure and conditioning agent, using the earthworm Californian Redworm (Eisenia foetida). For the cultivars, both lettuce and arugula, the height of seedlings, the diameter of the colon, dry mass of shoot, roots, and total were evaluated. There was no significant difference between the evaluated treatments in relation to the dry mass of the roots of Crespa cultivar lettuce, but for the American cultivar, the treatments using vermicompost with conditioning agent the sawdust or rice husk were superior to the commercial substrate in relation to dry mass of the roots. Among the cultivars of the arugula, no significant difference was observed between the treatments on the variables evaluated. Therefore, it is possible to conclude that substrates produced from vermicompost with sawdust and rice husks as conditioning agents can replace the commercial substrate during the production of lettuce and arugula.